The impact of formal and informal social controls on the criminal activities of probationers - MacKenzie, Doris Layton (Journal of research in crime and delinquency, 2002)
The monthly self-reported criminal activities, risk behaviors, and local life circumstances of offenders who began sentences of probation in northern Virginia were examined during the year prior to arrest, between arrest and probation, and during the first eight months of probation. The criminal activities and risk behaviors of the offenders declined dramatically after arrest and continued at this lower level throughout the probation period studied. When these offenders participated in high-risk behaviors such as carrying a gun, using drugs, and heavy use of alcohol, they committed more crimes; conversely, when they lived with spouses or were employed, they committed fewer crimes. There was no change in local life circumstances from the prearrest, arrest, and probation periods. The decline in criminal activities after arrest and during probation did not appear to be related to changes in informal social controls as measured by local life circumstances. The results were interpreted as consistent with a possible a deterrent effect